1999
DOI: 10.1046/j.1365-2168.1999.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complications after thyroidectomy and the need for tracheostomy in patients with a large goitre

Abstract: Multiple preoperative risk factors in a patient with a large goitre may be useful in predicting the need for planned tracheostomy following thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 4 publications
3
52
2
1
Order By: Relevance
“…4 Preoperatively, difficult intubation has been associated with tracheal deviation 5 and thyroid cancer. 6 If there is any concern regarding the potential for respiratory or ventilatory compromise, preoperative work-up should include chest x-ray and CT-scan of the neck and chest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Preoperatively, difficult intubation has been associated with tracheal deviation 5 and thyroid cancer. 6 If there is any concern regarding the potential for respiratory or ventilatory compromise, preoperative work-up should include chest x-ray and CT-scan of the neck and chest.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 These etiologies may have been contributing factors during the postoperative course. Tracheomalacia, though a common cause of postoperative airway obstruction, 4 was ruled out by direct palpation of the trachea following surgery. Although the recurrent laryngeal nerves appeared to be intact, the patient demonstrated weak left vocal cord movement postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…1 In another report from Sudan, 6 (5.8%) of 103 patients undergoing thyroid surgery for a large goiter had tracheomalacia, with 5 (4.8%) requiring a tracheostomy. 2 These and several other studies indicate a link between a longstanding goiter and tracheomalacia. 7,9-11 Conversely, Lacoste et al followed a cohort of 3,008 patients undergoing thyroidectomy and found that none of the cases developed tracheal collapse after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Airway obstruction after thyroidectomy is a rare but serious complication 2,3,7 which may lead to catastrophic consequences. The causes of airway obstruction specifically related to thyroid resection include postoperative wound hematoma, vocal cord palsy secondary to recurrent Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Difficulty with intubation may be caused by an enlarged thyroid gland producing tracheal deviation, compression, or both. [6] Amathieu et al [4] concluded that classical predictive criteria like mouth opening <35 mm, Mallampati III or IV, limited neck movements <80°, and thyromental distance were reliable predictors of difficult airway.…”
Section: Discussion:-mentioning
confidence: 99%